A proposed design solution for New Life Foundation Learning Center - Chua, Janelle Rose C.; Cruz, Agerico V. (1993.)
The existing problems of New Life Foundational Learning Center, a residential house has turned into a learning center in Paco, Manila were described and studied to better improve the learning environment of the children. Observations, interviews and personal experiences were used in data gathering. A design proposal was therefore formulated in order to achieve this goal.
Thesis (BID)--University of the Philippines Diliman.
Keywords: New Life Foundation Learning Center; Design -- Philippines